Base stacking and hydrogen bonding in protonated cytosine dimer: the role of molecular ion-dipole and induction interactions - Sponer, J; Leszczynski, J; Vetterl, V; Hobza, P (Journal of biomolecular structure & dynamics, 1996)
An ab initio quantum-chemical study of stacked and hydrogen-bonded protonated cytosine dimer has been carried out. The calculations were made using the second-order Moller-Plesset perturbational method (MP2) with a medium-sized polarized set of atomic orbitals. H-bonded as well as stacked protonated base pairs are more stable than the neutral base pairs. Two energy contributions not present in the neutral base pairs stabilize the protonated base pairs: the molecular ion - dipole interaction, and the induction interaction. The molecular ion - dipole stabilization dominates in base pairs with highly polar neutral monomers, such as the C...CH+ base pair. The induction interaction is not included in the commonly used empirical potentials, which do not reproduce the changes in intermolecular stabilization due to protonation. We demonstrate that the base stacking of several consecutive C...CH + pairs, as proposed for polycytidylic acid and i-DNA, is strongly repulsive. We also show that the intermolecular interactions strongly prefer protonation of adenine in protonated adenine-cytosine pairs.
Keywords: vodíková vazba; Cytosine; Mathematical Computing; zastoupení bazí; konformace nukleové kyseliny; Ions; Protons; cytosin; Nucleic Acid Conformation; Base Composition; protony; Hydrogen Bonding; DNA; matematické výpočty počítačové; ionty